HAFAZHATUL AMWAAL: TOKOH DAN KARAKTER AKUNTAN RASULULLAH - Ady Cahyadi (Department of Accounting-Faculty of Economic and Business (FEB), 2014)
The accountants are not a current profession only but a profession which areestablished since Rasulullah Muhammad Saw era. Rasulullah Saw especially treats andeducates his friends to be a clerk (katibul amwaal), accountant (hafazhatul amwaal) becausebeside as a prophet He is a good entrepreneur too. This article aims to explore the shirahnabawiyah (literature study) to give us who is the accountant in Rasulullah era and howabout their characteristic. Based on literature searches there are some companions of theProphet Muhammad are positioned specifically for financial management (state) Messengereven split into seven functions, six accounting function and one function to the examination(audit)DOI: 10.15408/akt.v7i2.2674